IMPLEMENTASI MEDIA KARTU ATURAN UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA KELAS I SD - Renis Suryaningrum; Sumadi; Sri Wahyuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to utilize Rule Cards to improve first-grade students' Pancasila Education learning outcomes on the school environment at the Sendangharjo IV Elementary School (SDN Sendangharjo IV Tuban) Technical Implementation Unit (UPT). This research uses the classroom action research (CAR) type. Twenty-eight first-grade students at the Sendangharjo IV Elementary School (UPT SD Negeri Sendangharjo IV Tuban) participated in the study. The research process involved planning, implementation, observation, and analysis, which were conducted in two phases. Observation sheets and tests were among the tools used. Data were analyzed using percentages. The results of this study indicate that first-grade students' Pancasila Education scores on the school environment at the Sendangharjo IV Elementary School (UPT SDN Sendangharjo IV Tuban) can be improved by utilizing the Rule Cards. The class completion rate increased from 50% in the first cycle to 85.71% in the second cycle. Therefore, the Rule Cards can help first-grade students at the Sendangharjo IV Elementary School (UPT SDN Sendangharjo IV Tuban) improve their Pancasila Education learning outcomes on the school environment.